Effect of Green Tea Extract on Histological Structure of Kidney, Pancreas and Adrenal Gland in Alloxan-Induced DiabeticMale Albino Rats - Al-Hilfy, Jabber Hameed Yenzeel (Al-Nahrain Journal of Science, 2018)
Histological structure of kidney, pancreas and adrenal gland in alloxan-induced diabetic rats was investigatedafter daily oral administration of green tea water extract for 4 weeks. Forty adultmale albino rats Rattusnorvegicus, 12 weeks old, weighing 150-160 g were divided into 4 experimental groups: The first group was considered as negative control group. The second groups were affected by inducing experimental diabetes by intraperitonial injection of (150 mg/kg b.w) alloxan. The third group was considered as positive control and treated with water extract of the green tea (200 mg/kg b.w), and the fourth group was affected by inducing diabetes and treated with green teaextract. Kidney, adrenal gland and pancreatic samples were obtained and processed for microscopic evaluation after staining the prepared sections with both Heamatoxylin and Eosin. No histological changes were found in the examined organs belong to rats treated with green tea, (+ve control) while there was a severe histopatholoigical changes like aggregation of inflammatory, neutrophil and monocytes around the blood vessels in kidney tissue, severe fatty degenerative in the adrenal gland and destruction of Island of Langerhans of diabetic rats group. The results showed less extensive histological changes like degeneration of the cells lining the kidney tubules, vaculation of glumerules, and weak fatty degeneration in cellslining of kidney tubules, also moderate fatty degenerative in pancreas tissue and adrenal gland were found in diabetic rat treated with green tea group. From these results it can be conclude that the consumption of green tea extract reduced the degenerative effects of alloxan in histological structures